(3GdeSFhdjI GdeOfjI Yf NOGY GdeSJgdc (B:s (3aj GdJTQjY GdEeGQGJj hGdeUQj hGdaQfSj habG dCMOK GdJYOjdGJ hCMcGe GdfbV hGdGJMGOjI GdYdjG hGdJejjR (B/s - (3jhSa, CTQa Cejf aQLs ((3GdbGgQI (B:s (3OGQ GdfgVI GdYQHjI ;s (3OHj, GdEeGQGJ GdYQHjI GdeJMOI (B:s (3OGQ GdfgVI GdYdejI,s, 2021)
(3jJfGhd cJGH (B((3GdeSFhdjI GdeOfjI Yf NOGY GdeSJgdc (B: (3aj GdJTQjY GdEeGQGJj hGdeUQj hGdaQfSj habG dCMOK GdJYOjdGJ hCMcGe GdfbV hGdGJMGOjI GdYdjG hGdJejjR(B) (3hGdPj bGe HJCdjag (B((3CTQa Cejf aQL jhSa(B) (3aj MhGdj (B(411) (3UaMI ef GdbWY GdeJhSW ehVhY (B((3ebGQfI bGfhf MeGjI GdeSJgdc aj eUQ haQfSG hGdEeGQGJ(B) (3eSJYQVG GdeMJhjGJ GdJGdjI (B: (3GdJegjOj (B: (3hSGFd NOGY GdeSJgdc, GdHGH GdChd (B: (3GdeSJgdc hGdeYdf Hjf GdOYGjI GdeVddI hGdEdJRGe HGdEYdGe, GdHGH GdKGfj (B: (3BdjGJ MeGjI GdeSJgdc ef GdNOGY hGdJVdjd, GdHGH GdKGdK (B: (3GdeSFhdjI GdeOfjI ddbGFe HNOGY GdeSJgdc(B.s
(3HHdjhLQGajI (B: (3UaMI (B393-410.s
Keywords: (3MeGjI GdeSJgdcs -- (3bhGfjf hJTQjYGJs -- (3GdEeGQGJ GdYQHjI GdeJMOIs; (3MeGjI GdeSJgdcs -- (3bhGfjf hJTQjYGJs -- (3eUQs; (3MeGjI GdeSJgdcs -- (3bhGfjf hJTQjYGJs -- (3aQfSGs; (3GdHjYs -- (3bhGfjf hJTQjYGJs -- (3aQfSGs; (3GdHjYs -- (3bhGfjf hJTQjYGJs -- (3eUQs; (3GdHjYs -- (3bhGfjf hJTQjYGJs -- (3GdEeGQGJ GdYQHjI GdeJMOIs; (3GdZT hGdJOdjSs -- (3bhGfjf hJTQjYGJs -- (3GdEeGQGJ GdYQHjI GdeJMOIs; (3GdZT hGdJOdjSs -- (3bhGfjf hJTQjYGJs -- (3eUQs; (3GdZT hGdJOdjSs -- (3bhGfjf hJTQjYGJs -- (3aQfSGs